2013
DOI: 10.1007/s00404-013-3019-1
|View full text |Cite
|
Sign up to set email alerts
|

Myomectomy during caesarean: a retrospective evaluation of 16 cases

Abstract: Myomectomy carried out during caesarean section is a trusted surgical intervention regardless of the size of leiomyomata.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
31
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 12 publications
2
31
0
3
Order By: Relevance
“…Studies on the safety of removal of myomas ≥5cm during C-section reported no difference between the groups in length of hospital stay, Hb changes and length of operation. 18,19 The mean diameter of myomas in our study was 66.3±30.2 mm. Among the operated patients, 24 (57.1%) had myomas with diameters ≤5 cm, 13 (30.9%) with diameters between >5cm and <10cm, and 5 (11.9%) with diameters ≥10cm.…”
Section: Discussionmentioning
confidence: 53%
“…Studies on the safety of removal of myomas ≥5cm during C-section reported no difference between the groups in length of hospital stay, Hb changes and length of operation. 18,19 The mean diameter of myomas in our study was 66.3±30.2 mm. Among the operated patients, 24 (57.1%) had myomas with diameters ≤5 cm, 13 (30.9%) with diameters between >5cm and <10cm, and 5 (11.9%) with diameters ≥10cm.…”
Section: Discussionmentioning
confidence: 53%
“…These studies have mostly been retrospective, with only a limited number of them being prospective in design. Cesarean myomectomy appears to be a safe procedure, as shown by retrospective studies involving small numbers of patients (8,17,20,21). Similarly, in a study that evaluated 368 patients with uterine fibroids, 111 patients underwent myomectomy and 257 patients underwent cesarean section only patients were selected for myomectomy using similar criteria as in a previous study.…”
Section: Discussionmentioning
confidence: 92%
“…In fact, recent medical literature, however, indicates that these procedures are probably feasible and reliable if correctly performed, as reported by Incebiyik et al [10]. In their study, the smallest leiomyoma was 5cm, while the largest was 22cm including the patient with 3.300cm 3 fibroid nodule, none of their cases was complicated during uterine repair, only two patients needed blood transfusion after CM.…”
mentioning
confidence: 75%